2021
DOI: 10.3390/en14164732
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Analysis in the Draft Tube of a Pump-Turbine under Steady and Transient Conditions

Abstract: Pumped-storage power stations play a regulatory role in the power grid through frequent transition processes. The pressure pulsation in the draft tube of the pump-turbine under transient processes is important for safe operation, which is more intense than that in the steady-state condition. However, there is no effective method to obtain the exact pressure in the draft tube in the transient flow field. In this paper, the pressure in the draft tube of a pump-turbine under steady-state and transient conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Ardizzon et al (2016) simulated the low-frequency components caused by the rotating stall phenomenon at low flow rates and found that the draft tube flow-state change is significant when the operating load is small. The vortex rope rotation frequency is generally 1/3-1/5 of the rotation frequency (Wang et al, 2017;Yang et al, 2021). Guo et al (2021) found that the smaller the guide vane opening, the more disordered the vortex generated in the mixed-flow turbine, thus affecting the efficient and stable operation of the turbine.…”
Section: Introductionmentioning
confidence: 99%
“…Ardizzon et al (2016) simulated the low-frequency components caused by the rotating stall phenomenon at low flow rates and found that the draft tube flow-state change is significant when the operating load is small. The vortex rope rotation frequency is generally 1/3-1/5 of the rotation frequency (Wang et al, 2017;Yang et al, 2021). Guo et al (2021) found that the smaller the guide vane opening, the more disordered the vortex generated in the mixed-flow turbine, thus affecting the efficient and stable operation of the turbine.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Cavazzini simulated the pressure fluctuation in the S-shaped region of a pump turbine and captured the low-frequency component caused by the rotating stall phenomenon at a low flow rate, which was induced by the rotating stall phenomenon [17,18]. By analyzing the pressure difference between the inner wall of the draft tube center and the inner wall, Yang et al determined the relation between the pressure pulsation values of the inner wall and that of the center wall of a draft tube [19]. Guo et al found that the smaller the opening of the guide vane, the more disordered the vortex generated by each part of the turbine, and the more unstable the flow field.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [18] studied the stability performance of PSH generation systems during the transition from condensing to generating mode, developed a mathematical model to describe this dynamic transition process, and effectively predicted the dynamic response of the system parameters. Finally, Yang et al [19] studied the relationship between the pressure pulsation value in the center of the pump-turbine draft tube and the wall pressure pulsation value using the CFD method. The study provided the critical value of the wall pressure pulsation when cavitation occurred, providing a reference for determining the cavitation phenomenon using the wall pressure pulsation value in practical engineering.…”
Section: Introductionmentioning
confidence: 99%